Differential regulation of microRNA stability - Bail, Sophie (Cold Spring Harbor Laboratory Press, 2010)
MicroRNAs (miRNAs) are endogenous single-stranded RNA molecules of about 21 nucleotides in length that are fundamental post-transcriptional regulators of gene expression. Although the transcriptional and processing events involved in the generation of miRNAs have been extensively studied, very little is known pertaining to components that regulate the stability of individual miRNAs. All RNAs have distinct inherent half-lives that dictate their level of accumulation and miRNAs would be expected to follow a similar principle. Here we demonstrate that although most miRNA appear to be stable, like mRNAs, miRNAs possess differential stability in human cells. In particular, we found that miR-382, a miRNA that contributes to HIV-1 provirus latency, is unstable in cells. To determine the region of miR-382 responsible for its rapid decay, we developed a cell-free system that recapitulated the observed cell-based-regulated miR-382 turnover. The system utilizes in vitro-processed mature miRNA derived from pre-miRNA and follows the decay of the processed miRNA. Using this system, we demonstrate that instability of miR-382 is driven by sequences outside its seed region and required the 3′ terminal seven nucleotides where mutations in this region increased the stability of the RNA. Moreover, the exosome 3′–5′ exoribonuclease complex was identified as the primary nuclease involved in miR-382 decay with a more modest contribution by the Xrn1 and no detectable contribution by Xrn2. These studies provide evidence for an miRNA element essential for rapid miRNA decay and implicate the exosome in this process. The development of a biochemically amendable system to analyze the mechanism of differential miRNA stability provides an important step in efforts to regulate gene expression by modulating miRNA stability.